Penentuan Energi Celah Pita (Band Gap) Nanopartikel ZnO/Au Hasil Ablasi Laser dalam Cairan - Mardiana Julita; Muhandis Shiddiq; Miftahul Khair (Departemen Kimia FMIPA UNP, 2023)
The synthesis of ZnO and ZnO/Au nanoparticles using the laser ablation method in liquid has been successfully carried out. Characterization of the optical properties of ZnO and ZnO/Au using a UV-Vis Spectrophotometer (Ocean Optic MAYA Pro 2000) which was measured in the wavelength range of 275 - 875 nm. The characterization results obtained are absorbance values and band gap values of ZnO and ZnO/Au nanoparticles. From this study, the absorbance values of ZnO nanoparticles were found at wavelengths of 330 and 335 nm. After obtaining the absorbance value, the band gap value was analyzed for ZnO and ZnO/Au nanoparticles, respectively, namely 3.23 eV and 3.17 eV. The decrease in the band gap value in ZnO is due to the presence of Au in ZnO nanoparticles which can replace one of the lattices in the ZnO crystal structure.